Motivational Impact and Value Perception of Digital Badges towards Applying for Jobs: Evidence from Indonesian Undergraduates - Pangaribuan, Christian Haposan; Febriyanto, Rahmat Arif (International Review of Management and Marketing, 2019)
In the age of competition for employers to acquire talents, especially when digitization takes place in just about everything, companies can implement digital badge to attract talents. The employers face a challenge of talents shortage in which employers hardly fill positions in the company. Despite the big number of graduates who are looking for jobs, this problem still arises because those graduates tend to be more selective in applying for jobs. In this study, the implementation of digital badge is examined through the perspective of Self-Determination Theory (SDT), which explains three types of motivation, i.e. amotivation, extrinsic motivation, and intrinsic motivation. The study aims to examine the influence of those three types of motivation on perceived value of digital badge and intention to send application to a company that implements digital badge. A quantitative approach is employed and final year college students and fresh graduates living in Greater Jakarta Metro Area or JABODETABEK (Jakarta, Bogor, Depok, Tangerang, and Bekasi) are studied. 411 samples are gathered and the study found that the three types of motivations influence perceived value of digital badge. However, only amotivation and perceived value of digital badge influence the intention to send application to a company that implements digital badge. Keywords: Digital Badge, Self-Determination Theory, Amotivation, Extrinsic Motivation, Intrinsic Motivation, Perceived Value JEL Classifications: J28, L2 DOI: https://doi.org/10.32479/irmm.8172